2016
DOI: 10.1186/s12879-016-1959-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of latent tuberculosis infection among migrant farmworkers along the US-Mexico border

Abstract: BackgroundMigrant farmworkers are among the highest-risk populations for latent TB infection (LTBI) in the United States with numerous barriers to healthcare access and increased vulnerability to infectious diseases. LTBI is usually diagnosed on the border using the tuberculin skin test (TST). QuantiFERON-TB Gold In-Tube (QFT-GIT) also measures immune response against specific Mycobacterium tuberculosis antigens. The objective of this study is to assess the comparability of TST and QFT-GIT to detect LTBI among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The frequency in males was 79.6% (537/674), given that most people who carry out activities associated with livestock production are usually male. This is coherent with other studies where the frequency of males was also high [9,17,2325]. Likewise, according to WHO, worldwide, men have a significantly higher risk of contracting TB compared to women [26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The frequency in males was 79.6% (537/674), given that most people who carry out activities associated with livestock production are usually male. This is coherent with other studies where the frequency of males was also high [9,17,2325]. Likewise, according to WHO, worldwide, men have a significantly higher risk of contracting TB compared to women [26].…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, Oren and collaborators analyzed 109 agricultural migrant workers from the US-Mexico border. They found that the prevalence of latent TB was 34% with TST and 50% with IGRA [17]. One of the possible reasons for the low frequency of latent TB found in this study may be the selected population.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…1 These farmworkers experience high rates of occupational injury and illness. 2,3 Many also experience chronic diseases, including diabetes, tuberculosis, and hypertension, [4][5][6][7][8] as well as significant mental health problems, including stress, depression, and alcohol use disorders. [9][10][11][12] However, these farmworkers have limited access to conventional health services.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Mexico reported 21 cases per 100,000 people [2], indicating that TB remains prevalent in the current population. Remarkably, the Northern States listed the highest incidence values, with Baja California at the forefront [12,13]. Here, we present a simple DNAzol–LAMP procedure for the detection of M. tuberculosis in sputum specimens.…”
Section: Introductionmentioning
confidence: 99%